HS 507 (Pusa Suketi): Low infection type stripe rust resistant high yielding wheat variety for Northern hills of India - Pal, Dharam; Kumar, Sanjay; Watpade, Santosh; Yadav, Ram Niwas; Sivasamy, M; Kumar, Jagdish (Journal of Cereal Research, 2025)
During the last few years, stripe rust (Puccinia striiformis) has become a major constraint in wheat production of Northern India. Low stripe rust infection type, high yielding wheat variety HS 507 (Pusa Suketi) was released by Central Sub-Committee on Crop Standards, Notification and Release of Variety for commercial cultivation under timely sown irrigated and rainfed conditions of Northern Hills Zone (NHZ). The wheat variety HS 507 has average grain yield of 4.68 t/ha under irrigated and 2.66 t/ha under rain fed timely sown condition of NHZ. This variety has shown resistance against a wide array of stripe rust pathotypes in Northern hills of India. The deployment of HS 507 at large scale not only increase wheat productivity in Northern hills but also reduce inoculum of stripe rust to the wheat crop grown in North-Western plains of India.Â Â